ANALISIS KOMITMEN ORGANISASI, IKLIM ORGANISASI DAN KEPUASAN KERJA PEGAWAI DI SEKRETARIAT JENDERAL KEMENTERIAN AGAMA RI - Eko Sugiyanto (Populis : Jurnal Sosial dan Humaniora, 2016)
Job satisfaction in an organization plays an important part in employees’ performance. It has connection with commitment and work atmosphere in the organization. With referrence to the previous study  on the issue within office of the Secretariat General of the Ministry of Religious Affairs of the Republic of Indonesia, there seem to exist problems in the issue. The paper further makes an account of job satisfaction in the organization. Using quantitative method, the finding of the study is that work atmosphere plays more significant part in maintaining job satisfaction among the employees of the Secretariat General of the Ministry of Religious Affairs than that contributed by commitment. Keywords : Organization’s commitment, work atmosphere, employees’ job satisfaction